The impact of the COVID-19 pandemic on medical education: adaptability and remote learning experience of the Peruvian American Medical Society - Valdivieso Rodríguez, Manuel (2023)
The COVID-19 pandemic had a significant impact on medical care and medical education in Peru.  In response, the Peruvian American Medical Society (PAMS), a charitable medical organization based in the USA, pursued its medical and educational missions in Peru by adopting virtual learning technology. We developed closer collaborative relationships with several medical schools and the Peruvian Association of Medical Schools (ASPEFAM) while offering a faculty panel of twenty-four members to provide lectures and multidisciplinary webinars in Spanish. We conducted 19 webinars including COVID -19 and non-COVID-19 related topics that over the last two years attracted 14,489 participants from 23 countries. They were the foundation for twenty publications in Peruvian medical journals. Our clinical investigations competition was positively received as was our pilot project on research mentorship. The COVID -19 pandemic had a positive effect on the educational mission of PAMS in Peru.